Targeting Microglia and Macrophages: A Potential Treatment Strategy for Multiple Sclerosis - Wang, Jiaying; Wang, Jiajia; Wang, Jincheng; Yang, Bo; Weng, Qinjie; He, Qiaojun (Frontiers in Pharmacology, 2019)
Multiple sclerosis (MS) is a chronic inflammatory neurodegenerative disease of the central nervous system (CNS). The early stage is characterized by relapses and the later stage, by progressive disability. Results from experimental and clinical investigations have demonstrated that microglia and macrophages play a key part in the disease course. These cells actively initiate immune infiltration and the demyelination cascade during the early phase of the disease; however, they promote remyelination and alleviate disease in later stages. This review aims to provide a comprehensive overview of the existing knowledge regarding the neuromodulatory function of macrophages and microglia in the healthy and injured CNS, and it discusses the feasibility of harnessing microglia and macrophage physiology to treat MS. The review encourages further investigations into macrophage-targeted therapy, as well as macrophage-based drug delivery, for realizing efficient treatment strategies for MS.